Pengembangan Sistem Pakar Identifikasi Modalitas Belajar Siswa Menggunakan Metode Forward Chaining dan Certainty Factor - Hardiansyah, Rudi; Aribowo, Didik; Hamid, Mustofa Abi (Building of Informatics, Technology and Science (BITS), 2022)
Teachers or educators find it difficult to determine student learning modalities at SMK PGRI 2 Serang City during online and offline learning. Online and offline learning must also be interesting and clear, not only images and text, but must be more interactive, because students have different learning modalities. So that in carrying out online learning the teacher must know the learning modalities of his students in order to make it easier to carry out online and offline learning. So it is necessary to create an expert system that can identify the learning modalities of students and also the accuracy of the expert system, the feasibility of efficient and effective learning modalities in online and offline learning. The stages of developing this website-based expert system design system use the waterfall method. The system development is in stages in 4 stages, namely the needs analysis stage, the design stage, the coding or implementation stage, and the system testing stage. The subjects in this study were 2 media experts, 4 teachers 1 school admin staff, and 36 students. Based on research results from testing the feasibility level of the system or product from media experts, namely 68.5 with these results it means the expert system website is in the "very feasible" category, then the results of testing the feasibility level of the expert system from users (teachers and students) are 94, 8 and 92.75 with these results in the "very feasible" category